Prospecção, caracterização molecular e conservação in vitro de Laeliinae (Orchidaceae) - Santos, Mariana de Souza (2014)
Orchids are ornamental plants cultivated by man long ago. The great diversity of colors and forms of the flowers of the species and natural and artificial hybrids adds to these plants high commercial value. The destruction of natural habitats, coupled with predation has led to the loss of genetic variability of the species, intensifying the already severe process of extinction.The aim of this study was to characterize native orchids of the SergipeState by ISSR molecular markers, as well as to study strategies for in vitro conservation under slow growth of three orchid species belonging to the subtribe Laeliinae. Two in vitro conservation experiments were realized, both in a completely randomized design. The first experiment was in a 3x3x2 factorial scheme, and we tested three combinations of carbon sources and osmotic regulators (20 g L-1of sucrose, 10 g L-1of sucrose + 5g L-1of mannitol, 10 g L-1of sucrose + 5g L-1of sorbitol), three orchid species (Epidendrum secundumJacq.,Encyclia dichroma (Lindl.) Schltr andCattleya tigrina A. Rich) and two temperatures (18 and 25°C).The second experiment was realized in a 4x3x2factorial scheme, and we tested four concentrations of salts of MS medium (100%, 75%, 50% and 25% of salts), three orchid species (Epidendrum secundumJacq.,Encyclia dichroma (Lindl.) Schltr andCattleya tigrina A. Rich) and two temperatures (18 and 25°C). The eight primers used in the study revealed a total of 87 fragments, all polymorphic, which proved effective in characterizing the collection of study. The diversity found within and between studied genera was high and promising for conservation studies.Cattleya tigrina presented 100% of survival at 180 days,and can be kept in medium with 25% of MS salts at 18°C. The temperature 18ºC also allowed the conservation of Epidendrum secundum for 365 days, with 100% of MS salts. Encyclia dichroma presented greater sensitivity to low temperature and can be kept at 25ºC with 25% of the salts of the MS medium for 365 days.